IFN-β mediates the anti-osteoclastic effect of bisphosphonates and dexamethasone - Kalkar, Prajakta; Cohen, Gal; Tamari, Tal; Schif-Zuck, Sagie; Zigdon-Giladi, Hadar; Ariel, Amiram (Frontiers in Pharmacology, 2022)
Zoledronic acid (Zol) is a potent bisphosphonate that inhibits the differentiation of monocytes into osteoclasts. It is often used in combination with dexamethasone (Dex), a glucocorticoid that promotes the resolution of inflammation, to treat malignant diseases, such as multiple myeloma. This treatment can result in bone pathologies, namely medication related osteonecrosis of the jaw, with a poor understanding of the molecular mechanism on monocyte differentiation. IFN-β is a pro-resolving cytokine well-known as an osteoclast differentiation inhibitor. Here, we explored whether Zol and/or Dex regulate macrophage osteoclastic differentiation via IFN-β. RAW 264.7 and peritoneal macrophages were treated with Zol and/or Dex for 4-24 hours, and IFN-β secretion was examined by ELISA, while the IFN stimulated gene (ISG) 15 expression was evaluated by Western blotting. RANKL-induced osteoclastogenesis of RAW 264.7 cells was determined by TRAP staining following treatment with Zol+Dex or IFN-β and anti-IFN-β. We found only the combination of Zol and Dex increased IFN-β secretion by RAW 264.7 macrophages at 4 hrs and, correspondingly, ISG15 expression in these cells at 24 hrs. Moreover, Zol+Dex blocked osteoclast differentiation to a similar extent as recombinant IFN-β. Neutralizing anti-IFN-β antibodies reversed the effect of Zol+Dex on ISG15 expression and partially recovered osteoclastic differentiation induced by each drug alone or in combination. Finally, we found Zol+Dex also induced IFN-β expression in peritoneal resolution phase macrophages, suggesting these drugs might be used to enhance the resolution of acute inflammation. Altogether, our findings suggest Zol+Dex block the differentiation of osteoclasts through the expression of IFN-β. Revealing the molecular pathway behind this regulation may lead to the development of IFN-β-based therapy to inhibit osteoclastogenesis in multiple myeloma patients.